UTILIZATION OF PRESENTATION PRACTICE PRODUCTION STRATEGY IN INSTRUCTING ENGLISH - Abduraxmonov Komiljon Mamurjon ugli (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes data almost a ponder that points to utilize unused strategy PPP amid the lessons and give openings for learners to utilize the target structure. Understanding of PPP strategy, preferences of PPP strategy and creating of this unused strategy.